Platelet rich plasma as a minimally invasive approach to uterine prolapse. (July 2017) - Chrysanthopoulou, E.L.; Pergialiotis, V.; Perrea, D.; Κourkoulis, S.; Verikokos, C.; Doumouchtsis, S.K.
Abstract: Pelvic organ prolapse (POP) is a major health problem that affects many women with potentially severe physical and psychological impact as well as impact on their daily activities, and quality of life. Several surgical techniques have been proposed for the treatment of POP. The FDA has published documents that refer to concerns about the use of synthetic meshes for the treatment of prolapse, in view of the severe complications that may occur. These led to hesitancy in use of these meshes and partial increase in use of other biological grafts such as allografts and xenografts. Although there seems to be an increasing tendency to use grafts in pelvic floor reconstructive procedures due to lower risks of erosion than synthetic meshes, there are inconclusive data to support the routine use of biological grafts in pelvic organ prolapse treatment. In light of these observations new strategies are needed for the treatment of prolapse. Platelet rich plasma (PRP) is extremely rich in growth factors and cytokines, which regulate tissue reconstruction and has been previously used in orthopaedics and plastic surgery. To date, however, it has never been used in urogynaecology and there is no evidence to support or oppose its use in women who suffer from POP, due to uterine ligament defects. PRP is a relatively inexpensive biological material and easily produced directly from patients' blood and is, thus, superior to synthetic materials in terms of potential adverse effects such as foreign body reaction. In the present article we summarize the existing evidence, which supports the conduct of animal experimental and clinical studies to elucidate the potential role of PRP in treating POP by restoring the anatomy and function of ligament support.